Bioorthogonal surface modified α-TCP-based bone filler for enhancement of apatite formation and bioactivity. Issue 5 (1st April 2019) - Moraveji, Marzie; Nezafati, Nader; Pazouki, Mohammad; Hesaraki, Saeed
Abstract: The aim of the present study was to investigate the effect of click chemistry reactants on morphology and physico-chemical properties of alpha tricalcium phosphate (α-TCP)-based powders. The powders were synthesized by solid-state reaction. The powders were modified with azide and cycloalkyne to form triazole as a consequence of reactions of these molecules. The presence of the band related to the triazole ring and the click molecules in powder structure was confirmed by Fourier transform infrared (FTIR) and Liquid chromatography- mass spectroscopy (LC-MS) analyses. Based on scanning electron microscopy (SEM) observations, the modified powder exhibited a different microstructure and morphology of apatite precipitates after one day and 7 days of soaking in distilled water and SBF solution, respectively, with respect to unmodified powder. According to the acellular in vitro test, X-ray diffraction (XRD) patterns represented triple characteristic peaks of hydroxyapatite (HA) in modified powder compared with control. Besides, the tendency of conversion of α-TCP to HA is more enhanced for modified powder as well. The SEM analysis depicted the plate-like and needle-like morphology of HA on the surface of modified and control powders, respectively. Since plate-like morphology of HA enhances bone generation and is found in trabecular bone, therefore, a future design can be considered for triazole-modified α-TCP-based fillers as good candidates for bone substitute application.